Opinions of Registered Nurses’ Towards Effective Nursing Management Related to the Retention of High Performance Employees: A Case Study of Nursing Department, Faculty of Medicine, Prince of Songkla University - ไกรวงศ์, นิตยา; จุฑาสันติกุล, วิภารัตน์; นวนสินธุ์, ทิพย์ราตรี (Princess of Naradhiwas University Journal, 2019)
The purpose of this descriptive study was to examine registered nurses’ opinions on factors that influence the retention of high-performance nurses in their organization. Sample was 273 registered nurses who were promoted to the highest level (A) of performance. Questionnaire on opinions towards management of high-performance employees was used to collect data. Frequency, percentage, mean and standard deviation were used in data analysis. The major findings were as follows: 1) Knowing nurses’ goals or expectations in terms of human development and career advancement was determinant to obtain the highest value with the highest average score (4.21 ± .57). 2) Supervisor’s report and discussion on nurses’ performance for every round of assessment received the highest average score (3.94 ± .76) with respect to nursing administrators and colleagues. 3) In terms of welfare, compensation and other environments, feeling secure in their job was highly ranked with the highest average score (3.92 ± .77) 4) Under the organization topic (nursing department), clear communication of organizational goals was highly valued with the highest average score (3.91 ± .64). In conclusion, the most important factor for the retention of high performance nurses was the opportunity for career advancement, particularly on the registered nurses’ awareness of the career goals and expectations.